2008
DOI: 10.1093/hmg/ddn132
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility locus for clinical and subclinical coronary artery disease at chromosome 9p21 in the multi-ethnic ADVANCE study

Abstract: A susceptibility locus for coronary artery disease (CAD) at chromosome 9p21 has recently been reported, which may influence the age of onset of CAD. We sought to replicate these findings among white subjects and to examine whether these results are consistent with other racial/ethnic groups by genotyping three single nucleotide polymorphisms (SNPs) in the risk interval in the Atherosclerotic Disease, Vascular Function, and Genetic Epidemiology (ADVANCE) study. One or more of these SNPs was associated with clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
124
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(135 citation statements)
references
References 24 publications
10
124
1
Order By: Relevance
“…These observations were in line with the report by Anderson et al (12), and suggested that variants at the 9p21 locus may robustly predict the prevalence of angiographic CAD, but not angiographic CAD severity. Assimes et al revealed that chromosome 9p21 variation was associated with total coronary plaque burden as expressed by calcification scores (13). However, angiographic CAD severity defined as number of stenotic coronary arteries appeared to correlate weakly with atherosclerotic plaque burden of the coronary tree.…”
Section: Discussionmentioning
confidence: 99%
“…These observations were in line with the report by Anderson et al (12), and suggested that variants at the 9p21 locus may robustly predict the prevalence of angiographic CAD, but not angiographic CAD severity. Assimes et al revealed that chromosome 9p21 variation was associated with total coronary plaque burden as expressed by calcification scores (13). However, angiographic CAD severity defined as number of stenotic coronary arteries appeared to correlate weakly with atherosclerotic plaque burden of the coronary tree.…”
Section: Discussionmentioning
confidence: 99%
“…9p21 was confirmed as a risk factor in the Korean (28 ), Japanese (28 ), and Chinese populations (29 ). In a study involving a large number of Southeast Asians, Assimes et al (30 ) showed that 9p21 was a CAD risk factor with features similar to those shown in the Caucasian studies; however, African Americans did not exhibit 9p21 as a risk factor in this study (30 ). In a more recent study, the Coronary Artery Disease Genetics Consortium (31 ) performed a GWAS of a discovery population of 30 482 individuals that included 6996 cases of South Asian ancestry from Pakistan and India, with replication in a sample size of 40 593 individuals that included 6187 South Asians.…”
Section: P21: a Risk Factor In All Ethnic Groups Except African Amermentioning
confidence: 93%
“…These groups appear not to have had the time to intermingle and break up the DNA haplotype that carries the risk. In contrast, in Africans, who have had a much longer history, the 9p21 risk region (haplotype) has been broken into smaller haplotypes that produce minimal or no risk for CAD (30 ).…”
Section: P21: a Risk Factor In All Ethnic Groups Except African Amermentioning
confidence: 99%
“…[5][6][7][8] These data for the first time were replicated in several cohorts of different ethnic origin, confirming the robustness of the results. [9][10][11][12][13][14] Moreover, they have been validated in a meta-analysis, performed on 12,000 cases and 29,000 controls, which showed a relative risk of 1.27 (95% CI 1.23-1.31; p=1.62 10 -12 ) for ischemic heart disease in the presence of each risk allele. [15] All currently identified risk alleles are relatively frequent.…”
Section: The Genetic Region 9p21mentioning
confidence: 94%
“…It has been hypothesized that aggregating the contributions of multiple SNPs into a single genetic risk score, combining the relatively small effect of individual genes, may help to identify the individual risk and increase the probability of predicting myocardial infarction beyond traditional risk factors. [13,14] However, the attempts made so far have led to mixed results and there are still few solid data supporting the clinical usefulness of such a scoring system. [19,[25][26][27][28] Kathiresan et al [25] tested the hypothesis that a combination of nine genetic variants associated with increased blood lipid levels into a genotype score contributes to the risk prediction of cardiovascular disease.…”
Section: The Role Of Genetic Markers On Cardiovascular Risk Predictionmentioning
confidence: 99%